Performance Evaluation of OTFS over EVA, ETU, and UAV Channels with Delay Doppler Grid Variations for High-Mobility Communications - Muhammad Idrus Syaban; Endah Setyowati (Universitas Islam Indragiri, 2026)
Orthogonal Time Frequency Space (OTFS) is a modulation scheme designed to improve the reliability of wireless communications in high-mobility environments, where transmission performance is significantly affected by Doppler effects. This study evaluates the performance of OTFS over three high-mobility channel models: Extended Vehicular A (EVA), Unmanned Aerial Vehicle (UAV), and Extended Typical Urban (ETU), with a particular focus on the impact of Delay-Doppler grid size on the bit error rate (BER). Simulations were conducted using Quadrature Phase Shift Keying (QPSK) modulation with a carrier frequency of 5.9 GHz, user mobility of up to 350 km/h, and a signal-to-noise ratio (SNR) ranging from 0 to 20 dB. The results show that increasing the Delay-Doppler grid size from 16 × 16 to 32 × 32 reduced the BER from the order of 10⁻³ to 10⁻⁴ across all channel models. However, further increasing the grid size beyond 32 × 32 resulted in only marginal performance improvements, indicating a saturation effect. These findings demonstrate that a 16 × 16 Delay-Doppler grid is sufficient to achieve reliable performance in high-mobility communication environments. Nevertheless, increasing the grid size to 32 × 32 provides superior performance by further reducing the BER, thereby offering an optimal balance between transmission reliability and computational complexity.